Histórias da terapia ocupacional na América Latina: processos de criação dos primeiros programas de formação profissional - Monzeli, Gustavo Artur (2019)
The thesis formulated here is based on questions about the reasons for the emergence or implantation of occupational therapy in Latin America and how the stories involving such processes are reduced to the reproduction of the history of the United States of America as if their reasons and contexts had been the same. The assumption that guided us was the search for the specific reasons in the different countries of the continent, in the Latin American. The general objective was to investigate the historical processes of creation of the first educational program in occupational therapy in each of the 14 countries that are members of the Latin American Confederation of Occupational Therapists. For this, the data presented here and discussed were constructed in four main stages: 1) design of the countries participating in the research; 2) identification of the participants, with the use of questionnaires and interviews; 3) search of historical records and scientific productions on the history of occupational therapy in each country; 4) analysis of the data produced by the questionnaires, interviews and historical records. The results of this thesis are evident in the discussion of historical pathways, from the creation of occupational therapy in the United States at the beginning of the 20th century, to the analysis of the main historical antecedents that provided the creation of the first professional training programs in Latin America countries from the 1950s onwards. The data analysis was proposed in eight dimensions: 1) the replication of educational programs models influenced by rehabilitation prospects of the Northern countries; 2) the formation of programs subordinated to medical logic; 3) the public for the educational programs composed mainly of women from urban elites to carry out social and humanitarian aid work; 4) the influence of World Federation of Occupational Therapy in determining guidelines for the curricula of new training programs; 5) international cooperation projects for the development of Latin America, mainly carried out by international organizations such as the UN, WHO, PAHO and ILO, which have contributed to the creation of standardized responses to the demands of rehabilitation; 6) regional cooperation, also mediated by international cooperation agencies, offering assistance for the graduation of professionals from other Latin American countries; 7) the professors of these first programs are, besides medics and occupational therapists from other countries, newly graduated occupational therapists, almost always from the training programs themselves; 8) the relation between the creation of the first educational programs and the political, economic and social situation in each country, which in some cases causes educational programs to to be boosted or receives little investment, mainly by the interest of States in developing, or not, strategies of care for the subjects and groups, in general, non-priority. The main conclusions allow us to point to the analysis of occupational therapy, at least in the scope of educational programs, as a product of the articulation between nation-states, by the logic of capital articulated to Coloniality.